Is there a linkage between sustainable development and market access of LDCs? - Tania, Sharmin (Walter de Gruyter GmbH, 2013)
This article revisits the decades-long trade-sustainable development debate in the context of Rio+20 and its endorsement of green economy policy. It aims to grapple with the possible linkages between LDCs' market access regime and the concept of sustainable development itself. Conflicting perceptions of developed and least developed country (LDC) members of the WTO as to the conceptual basis of sustainable development, this article argues, explain the challenges LDCs face in the form of impediments to their market access. By examining the specific market access issues, this article reveals how developed countries' concerns for sustainable development turn out to be market access barriers for LDCs. As the call for transition to green economy could exacerbate some of these concerns of LDCs, the article suggests a common ground, where a balanced trading regime can be most productively envisioned through a reasoned discourse of market access for LDCs linked with a conceptual route of sustainable development.